Source apportionment of aerosol measured in the northern South China Sea during springtime - Atwood, Samuel A., author; Kreidenweis, Sonia M., advisor; van den Heever, Susan C., committee member; Peel, Jennifer L., committee member (Colorado State University. Libraries, 2012)
Large sources of aerosol are known to exist in Asia, but the nature of these sources and their impacts on surface particulate matter concentrations are presently not well understood, due in part to the complex meteorology in the region and the lack of speciated aerosol observations. This work presents findings from a pilot study that was aimed at improving knowledge in these areas. Aerosol was collected at a sea-level surface site using an 8-stage DRUM cascade impactor during an approximately six week study at Dongsha Island in the northern South China Sea in the Spring of 2010. The samples were analyzed by X-ray fluorescence (XRF) for selected elemental concentrations, and factor analysis was performed on the results using principal component analysis (PCA). The six factors extracted by PCA were identified as various dust, pollution, and sea salt aerosol types. A refined coarse mode only factor analysis yielded three coarse factors identified as dust, pollution laden dust, and sea salt. Backtrajectory analysis with the HYSPLIT trajectory model indicated likely source regions for dust factors to be in western and northern China and Mongolia, consistent with the known dust sources in the Gobi and Taklimakan Deserts. Pollution factors tended to be associated with transport from coastal China where large population and industrial centers exist, while sea salt sources indicated more diffuse marine regions. The results were generally consistent with observations from a co-located three-wavelength nephelometer and AERONET radiometer, along with model predictions from the Navy Aerosol Analysis and Prediction System (NAAPS). Backtrajectories indicated that transport of aerosol to the surface at Dongsha was occurring primarily within the boundary layer from regions generally to the north; an observation consistent with the dominance of pollution and dust aerosol in the ground-based data set. In contrast, more westerly flow aloft transported air from regions to the south and west, where biomass burning was a more significant aerosol source; however, this particle type was not clearly identified in the surface aerosol composition, consistent with it remaining primarily aloft and not mixing strongly to the surface during the study. Significant vertical wind shear and temperature inversions in the region support this conceptual understanding and suggest the potential for considerable vertical inhomogeneity in the SCS aerosol environment.
Keywords: aerosol vertical distributions; Asian aerosol; biomass burning aerosol; dust aerosol; factor analysis; marine aerosol